Forest harvesting and transport: Old problems, new solutions - Dykstra, D.P.; Heinrich, R. (1997)
Forest harvesting and transport operations lie on a near-optimal path for creating conflict. Thus their careful implementation is important not only for the sustainability of forests but also for the continuation of forestry as a profession. This paper summarises recent initiatives to reduce environmental and social impacts associated with forest harvesting and transport. These include efforts to reduce the global extent of harvesting operations in natural forests by increasing forest yields; attempts to enhance economic efficiency through better operational planning and control and through more effective training of forest workers; initiatives to develop incentive systems and policies which will promote the adoption of reduced-impact harvesting and transport system; efforts to prepare local and regional guidelines for environmentally sound forest practices; and work on the development of procedures of assessing the sustainability of forest practices. The paper also reviews briefly a selection of recent technological advances which promise to make forest harvesting and transport operations both more economically efficient and also more environmentally sound.